Developing Primary School Management in the Kingdom of Saudi Arabia based on self-management: Proposed Model - Al-Bishr, Fatima Abdullah; Alotaibi, Ibtisam Wajib; Alsuwaie, Sarah Abdullah (Journal of Educational and Psychological Sciences, 2024)
The study aimed to design a proposed model to develop primary school management in the Kingdom of Saudi Arabia based on self-management by investigating its reality and challenges. The study utilized a descriptive approach and a questionnaire to collect data from a sample of 25 primary school leaders in Saudi Arabia. Findings revealed that the reality of primary school management based on self-management had a "high" agreement degree, with a mean of 2.37 out of 3.0. The professional development of teachers was the highest-rated aspect, followed by accountability, effective communication, local community partnership, delegation of powers, and decision-making participation. Challenges to developing primary school administration based on self-management had an "intermediate" agreement degree, with a mean of 2.27 out of 3.0. Financial challenges ranked first, followed by administrative-organizational and human challenges. The study proposed a model for developing primary school administration based on self-management and recommended promoting a culture of self-management among school staff and supporting the Ministry of Education in implementing self-management in government schools.
Keywords: Developing primary school administration; self-management